2021
DOI: 10.1111/joa.13464
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture and passive lengthening properties of the gastrocnemius medialis and Achilles tendon in children who idiopathically toe‐walk

Abstract: Children who idiopathically toe‐walk (ITW) habitually operate at greater plantarflexion angles and thus, at shorter muscle‐tendon unit (MTU) lengths than typically developing (TD) children. Therefore, it is often assumed that habitual use of the gastrocnemius muscle in this way will cause remodelling of the muscle‐tendon architecture compared to TD children. However, the gastrocnemius muscle architecture of children who ITW has never been measured. It is essential that we gain a better understanding of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Despite being more plantarflexed, the moment-fascicle length relationship shifted significantly towards longer fascicle lengths in children who ITW (Figure 2b). This is consistent with recent findings showing that the passive gastrocnemius fascicle lengths were longer in children who ITW than TD children (Harkness-Armstrong et al, 2021), and corresponded with the ranges used during gait. Consequently, children who ITW and TD children both operated at similar joint angles and fascicle lengths relative to their respective measured optimum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite being more plantarflexed, the moment-fascicle length relationship shifted significantly towards longer fascicle lengths in children who ITW (Figure 2b). This is consistent with recent findings showing that the passive gastrocnemius fascicle lengths were longer in children who ITW than TD children (Harkness-Armstrong et al, 2021), and corresponded with the ranges used during gait. Consequently, children who ITW and TD children both operated at similar joint angles and fascicle lengths relative to their respective measured optimum.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we should not assume that the muscle functional properties are similarly affected in children who ITW. Indeed recently, we showed that children who ITW had longer resting absolute and normalised gastrocnemius medialis muscle belly and fascicle lengths than typically developing (TD) children (Harkness-Armstrong et al, 2021). This is the exact opposite effect to that found in children with CP.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, additional research is also required on the involvement of the intestinal microbiota of children with IWT in the development of Achilles tendon stiffness. The development of Achilles tendon stiffness and shortening in several children with ITW, together with habitual use of the gastrocnemius muscle and changes in the acting load, can lead to remodeling of the muscle-tendon architecture and the formation of equinus contracture [172][173][174].…”
Section: Gut Microbiota Diet and Exercisementioning
confidence: 99%
“…For the contracture model, the optimal fibre lengths and tendon slack length were obtained by minimising the root mean square error between the gastrocnemius and soleus passive moment-angle curve of the model and the 20 • shifted curve Musculotendon parameters were initially scaled such that the original force-length curves were maintained (Modenese et al, 2016). Next, for ITWs the generic passive ankle moment-angle curves for the gastrocnemii and soleus were shifted by 20 • into plantarflexion (Figure 1), because the maximum passive dorsiflexion range in ITWs was ∼20 • smaller than for TD children (Harkness-Armstrong et al, 2021b). When replicating the moment-length curves from Harkness-Armstrong et al (2021a; Figure 2a) using simulations with maximum activations at all joint angles, the moment-length curves did not reach a descending limb and stayed below optimal fibre length (Figure 2b).…”
Section: F I G U R Ementioning
confidence: 99%